An objective method to quantify elbow flexor spasticity using surface EMG and 3D motion analysis - Thielen, Mirjam; Pennekamp, Anna; Glaser, Julia; Harhaus-Wähner, Leila; Kneser, Ulrich; Grützner, Paul Alfred; Trinler, Ursula (Journal of electromyography & kinesiology, 2025)
Spasticity in the upper extremities, particularly elbow flexor spasticity, significantly impairs motor control. Evaluating the extent of spasticity is crucial for effective therapy planning and assessing treatment outcomes. However, there are currently no accurate and reliable measures to quantify upper extremity spasticity. This study aims to introduce an instrumented assessment method for evaluating elbow flexor spasticity using an integrated approach tailored for spasticity assessment. This clinical study included 17 patients with elbow flexor spasticity (mean age 40 ± 20 years) and 20 arms of 10 healthy adults (mean age 33 ± 8 years). The elbow flexors were passively stretched at low and high velocities, and kinematic data were recorded using 3D motion analysis (U.L.E.M.A. model). Muscle excitations of the biceps brachii were assessed via surface EMG. Outcome parameters included the maximum elbow extension deficit during slow and fast passive stretch, EMG data normalized to maximum voluntary isometric contraction (MVIC) at low and high velocities, and the difference between the two (EMGchange). All outcome parameters showed significant differences (p < 0.05) between patients with elbow flexor spasticity and healthy adults. The proposed instrumented assessment tool is a suitable measurement method for evaluating elbow flexor spasticity.